Research on model application to restructuring the railway transport sector in Lithuania - Jarašūnienė, Aldona (Transport, 2009)
There is no economic grounding and estimation of costs incurred to the State by the establishment and operation of the railway infrastructure management enterprise. In this regard, the article deals with the evaluation of reforming the railway transport sector in other countries and analyses the comparison of restructuring models according to the experience of the EU member states as well as evaluates the selection of models proposed by foreign theoreticians and from an economic point of view justifies the most relevant model of reforming Lithuanian railway transport sector.First published online: 27 Oct 2010